Cognition in epilepsy patients with hypothalamic hamartomas. (June 2017) - Wagner, Kathrin; Wethe, Jennifer V.; Schulze‐Bonhage, Andreas; Trippel, Michael; Rekate, Harold; Prigatano, George P.; Kerrigan, John F.
Summary: Many patients with epilepsy caused by hypothalamic hamartomas (HHs) have cognitive impairments during the course of the disease or following neurosurgical treatment. The purpose of this study was to assess cognitive function in these patients, as well as factors influencing preoperative cognitive performance and cognitive outcome after neurosurgical treatment. Using the two largest and most detailed neuropsychology datasets on HH and epilepsy from two centers, we retrospectively report on cognitive functions in 48 patients with structural epilepsy due to HH (mean age ± standard deviation [SD] 20 ± 12 years, range 5–53 years, median 16 years; disease duration mean 17 ± 11 years). Intelligence, verbal learning and recall, and speed and executive functions (processing speed and cognitive flexibility) were assessed before and on average 19 (±11) months after surgery (interstitial radiosurgery: N = 22; neurosurgical resection/disconnection: N = 26). Prior to neurosurgical treatment, 52% of patients showed impaired executive and 62% showed reduced verbal memory functions. A trend for a detrimental effect of higher drug load on cognitive functioning was found. After neurosurgical treatment, intellectual functions for the entire cohort tended to increase. This correlated with improved seizure frequency and decreased number of antiepileptic drugs (AEDs). However, postoperative outcomes for individual patients were highly variable, with significant deteriorations in 17% (processing speed) to 34% (cognitive flexibility and verbal learning), and performance increases in 17% (intellectual functioning) up to 39% (processing speed) of the patients. Higher levels of presurgical performance were significant predictors of cognitive decline after surgery. These results are highly relevant for patient consultation and may help with therapeutic decisions.